المعالجة الإشعاعية للمزائج EPDM – LLDPE)) - منصور, رامي; علي, علي; غانم, مصعب (Latakia University Journal -Engineering Sciences Series, 2019)
تمّ إجراء عمليّة تشابك المزائج (EPDM/LLDPE) ذات نسب المزج المختلفة من خلال المعالجة الإشعاعيّة لهذه المزائج بأشعّة غاما، وقد تبيّن أنّ زيادة تركيز LLDPE في المزائج يحسّن الخواصّ الميكانيكيّة لهذه المزائج، كما لوحِظ ازدياد كل من مقاومة الشدّ والقساوة في المزائج مع ازدياد قيمة الجرعة الإشعاعيّة إلى 200KGy نتيجة ازدياد كثافة التشابك العرضي للسلاسل الجزيئيّة التي يستدلّ عليها من الزيادة المستمرّة في محتوى الجل مع ازدياد قيمة الجرعة الإشعاعيّة بعد الغمر في مذيب التولوين، بينما لوحظ ازدياد قيمة الاستطالة عند الانقطاع Eb في المزائج المحتوية على نسب مختلفة من EPDM بشكل بسيط عند التشعيع بجرعاتٍ منخفضة (£ 70 KGy)ومن ثمّ تأخذ بالتناقص مع ازدياد الجرعة الإشعاعيّة إلى 300KGy. Radiation cross-linking of (EPDM-LLDPE) blends has been carried out by gamma radiation. It has been found that the addition of LLDPE improves the mechanical properties of EPDM; it has also been concluded that the tensile strength and hardness of these blends increases rapidly by increasing an absorbed dose up to 200KGy and starts to decrease or level off with further increase of radiation dose up to 300KGy. This behavior is believed to be due to the formation of radiation – induced cross-linking in the components is evidenced by the gel content value. The values of elongation at break (Eb) of the blends containing different concentrations of the EPDM increase slightly and reach a maximum value at the irradiation dose of (£ 70 KGy). Then, the value of Eb decreases with increasing the irradiation dose up to 300 KGy .